HUBUNGAN PENGETAHUAN DAN PERILAKU DIET DENGAN KEPATUHAN DIET PADA PASIEN DIABETES MELITUS TIPE II DI UPT PUSKESMAS CIRUAS SERANG - Marina Indriasari; Renan Prasta Jenie; Erny Siregar (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: WHO data, the prevalence of diabetes in the adult population aged 20–79 years in Indonesia is estimated to reach 10.6%. Meanwhile, data from the UPT Puskesmas Ciruas shows a rising trend in the prevalence of Type II Diabetes Mellitus, which was around 0.24% in 2020, increasing to 0.29% in 2021 (152 cases), and reaching 0.37% in 2022 (195 cases) from the total population of the work area. The increase in the prevalence of Type II Diabetes Mellitus, influenced by unhealthy eating habits, highlights the importance of studying the relationship between knowledge and dietary behavior with dietary compliance among patients at UPT Puskesmas Ciruas Serang.Objectives: The aim of this research was to determine the correlation of knowledge and behavior to dietary compliance and patients with diabetes mellitus type 2 at the Ciruas Public Health Center, Serang.Methods: Using descriptive analytical design with a quantitative method employing a cross-sectional research design. The research population consists of all type 2 diabetes sufferers visiting the nutrition clinic at UPT Puskesmas Ciruas, totaling 130 people. The sample was determined using the Slovin formula, resulting in 103 respondents through simple random sampling. The research instrument was a structured questionnaire regarding knowledge, dietary behavior, and dietary compliance. Data analysis was conducted univariately and bivariately using the Chi-Square test with a significance level of 0.05.Results: There was a relationship between knowledge and adherence to dietary compliance in patient with Type 2 Diabetes Mellitus at the Ciruas Public Health Center. The statistical test resulted obtained a p value = 0.018 < 0.05). There was a relationship between dietarybehavior and adherence to a dietary compliance in patients with Diabetes Mellitus type 2 at the Ciruas Health Center. The statistical test resulted obtained a p value = 0.023 < 0.05).Conclusion: This study shows that most type II DM patients at the Ciruas Community Health Center have poor knowledge, behavior, and dietary compliance. The analysis results prove a significant relationship between dietary knowledge (p=0.018) and dietary behavior (p=0.023) with adherence to the diet. Thus, increasing knowledge and improving dietary behavior play an important role in supporting dietary compliance in type II DM patients.Keywords : Behavior;diabetes mellitus type II; dietary compliance; knowledge ABSTRAKLatar belakang: Data WHO, prevalensi diabetes pada populasi dewasa usia 20–79 tahun di Indonesia diperkirakan mencapai 10,6%. Sementara itu, data di UPT Puskesmas Ciruas menunjukkan tren peningkatan prevalensi Diabetes Mellitus Tipe II, yaitu sekitar 0,24% pada tahun 2020, meningkat menjadi 0,29% pada tahun 2021 (152 kasus), dan mencapai 0,37% pada tahun 2022 (195 kasus) dari total populasi wilayah kerja. Peningkatan prevalensi Diabetes Mellitus Tipe II yang dipengaruhi oleh pola makan tidak sehat menunjukkan pentingnya meneliti hubungan pengetahuan dan perilaku diet dengan kepatuhan diet pada pasien di UPT Puskesmas Ciruas Serang.Tujuan: Untuk mengetahui Hubungan Pengetahuan Diet Dan Perilaku Diet Dengan Kepatuhan Menjalankan Diet Pada Penderita Diabetes Melitus Tipe II di UPT Puskesmas Ciruas, Serang.Metode: Menggunakan desain deskriptif analitik menggunakan metode kuantitatif dengan pendekatan desain penelitian Cross Sectional. Populasi penelitian adalah seluruh penderita DM tipe 2 yang berkunjung ke poli gizi UPT Puskesmas Ciruas sebanyak 130 orang. Sampel ditentukan dengan rumus Slovin, diperoleh 103 responden melalui simple random sampling. Instrumen penelitian berupa kuesioner terstruktur mengenai pengetahuan, perilaku diet, dan kepatuhan diet. Analisis data dilakukan secara univariat dan bivariat menggunakan uji Chi-Square dengan tingkat signifikansi 0,05.Hasil: Terdapat hubungan Pengetahuan dengan kepatuhan menjalankan diet pada penderita Diabetes Melitus Tipe II di UPT Puskesmas Ciruas. Hasil uji statistik diperoleh nilai p= 0,018< 0.05). Terdapat hubungan hubungan Perilaku diet dengan kepatuhan menjalankan diet pada penderita Diabetes Melitus Tipe II di UPT Puskesmas Ciruas. Hasil uji statistik diperoleh nilai p= 0,023< 0.05).Simpulan: Penelitian ini menunjukkan bahwa sebagian besar penderita DM tipe II di UPT Puskesmas Ciruas memiliki pengetahuan, perilaku, dan kepatuhan diet yang kurang baik. Hasil analisis membuktikan adanya hubungan signifikan antara pengetahuan diet (p=0,018) dan perilaku diet (p=0,023) dengan kepatuhan menjalankan diet. Dengan demikian, peningkatan pengetahuan dan perbaikan perilaku diet berperan penting dalam mendukung kepatuhan diet pada penderita DM tipe II.Kata Kunci : Diabetes mellitus tipe II; pengetahuan; perilaku; kepatuhan diet